FATHERLESS: LUKA TERSEMBUNYI AKIBAT PERCERAIAN YANG MEMPENGARUHI PERILAKU REMAJA - Shania Aulia Rahmania Anshary; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
One of the countries included in the fatherless country category is Indonesia. The term